Fundamental Of Entrepreneurship (ENT300) : Proposal cafe and books / Hixmmien Mujah … [et al.]. - Mujah, Hixmmien; Uslan, Nalisha Laila; Jelian, Christina Bunsi; Yong, Sendy; Jadan, Eurecca (2011)
Our company name is CAFE AND BOOKS. The business of our company has been decided on the form of partnerships. Each partner has contributes certain amount of capital as agreed in our agreement. Our main business activity is to offers services by selling and renting books as well as re-selling used books and offer services ofselling food and beverages in our cafe.